F-a sentence example

f-a
  • �; S = r A F(a 0, 711, a2,���bo, b l, b 2,���9���; xl, x2), viz.
    0
    0
  • Thus f t2 ds (for A) = f A ds (for B)..
    0
    0
  • If we take the axis of z normal to either surface of the film, the radius of curvature of which we suppose to be very great compared with its thickness c, and if p is the density, and x the energy of unit of mass at depth z, then o- = f o dz, (16) and e = f a xpdz,.
    0
    0
  • N was i n f a v o u r o u r of inviting him.
    0
    0
  • N was i n f a v o u r of inviting him.
    0
    0
    Advertisement
  • �; S = r A F(a 0, 711, a2,���bo, b l, b 2,���9���; xl, x2), viz.
    0
    0